Probiotics for the treatment of depression and anxiety: A systematic review and meta-analysis of randomized controlled trials - El Dib, Regina [UNESP]; Periyasamy, Aravind Gandhi; de Barros, Jessica Lima [UNESP]; França, Carolina Gonzales [UNESP]; Senefonte, Fernanda Labiapari [UNESP]; Vesentini, Giovana [UNESP]; Alves, Mônica Ghislaine Oliveira; Rodrigues, João Vitor da Silva [UNESP]; Gomaa, Huda; Gomes Júnior, José Reinaldo [UNESP]; Costa, Lucas Fernandes; Von Ancken, Thainá de Souza [UNESP]; et al. (Elsevier, 2021)
Background & aim: Probiotics in the gut have been suggested to have a beneficial effect on anxiety response and depressive disorder. Hence we conducted a systematic review and meta-analysis to summarize the effects of probiotics associated with or without pharmacological or psychological therapies in patients with depressive and/or anxiety symptoms or disorders. Methods: We conducted searches of MEDLINE, EMBASE, CENTRAL, PsycINFO, CINAHL, ProQuest, LILACS, and Web of Science up to February 2020 to identify randomized controlled trials (RCTs) investigating the efficacy of probiotics associated with or without pharmacological or psychological therapies for patient-important outcomes including relief of depressive, anxiety and stress symptoms, cognitive functions, adverse events and quality of life. We used the GRADE approach to rate the overall certainty of the evidence by outcome. The protocol of the systematic review was registered with PROPSERO and published under the number CRD4202016329. Results: 16 RCTs including 1,125 patients proved eligible. Results suggested a significant improvement in using Beck Depression Index (MD, −3.20 [95% CI, −5.91 to −0.49], p = 0.02; I2 = 21%, p = 0.28) for depression symptoms and State-Trait Anxiety Inventory (STAI) (MD, −6.88 [95% CI, −12.35 to −1.41], p = 0.01; I2 = 24%, p = 0.25) for anxiety with overall certainty in evidence rated as moderate and low, respectively. However, Depression Scale (DASS-Depression) (MD, 2.01 [95% CI, −0.80 to 4.82], p = 0.16; I2 = 0%, p = 0.62), Montgomery-Asberg Depression Rating Scale (MADRAS) (MD, −2,41 [95% CI, −10,55 to 5,72], p = 0,56; I2 = 87%, p = 0,006), Anxiety scale (DASS-Anxiety) (MD, 0.49 [95% CI, −4.05 to 5.02], p = 0.83; I2 = 74%, p = 0.05), and Stress Scale (DASS-Stress) (MD, 0.84 [95% CI, −2.64 to 4.33], p = 0.64; I2 = 34%, p = 0.22) showed no significant decrease in the relief of depression, anxiety and stress symptoms of probiotics compared to placebo with overall certainty in evidence rated as very low for all outcomes. We also found no differences in the Beck Anxiety Index (BAI) (MD, −3.21 [95% CI, −6.50 to 0.08], p = 0.06; I2 = 0%, p = 0.88) with overall certainty in evidence rated as low. Results suggested a non-statistically significantly effect of probiotics in the adverse events outcomes. Conclusions: The current review suggests that probiotics may improve symptoms of depression and anxiety in clinical patients. However, given the limitations in the included studies, RCTs with long-term follow-up and large sample sizes are needed.
Keywords: Anxiety; Depression; Probiotics; Randomized controlled trials; Stress; Systematic review